1999
DOI: 10.7863/jum.1999.18.4.303
|View full text |Cite
|
Sign up to set email alerts
|

Polycystic ovarian syndrome: assessment with color Doppler angiography and three-dimensional ultrasonography.

Abstract: We conducted a three‐dimensional ultrasonographic evaluation of the size and structure of the ovaries of women who had clinical and biochemical findings suggestive of polycystic ovary syndrome. We carried out a comparative color Doppler frequency and color Doppler amplitude study of the vascular patterns of these ovaries. This study involved 65 women of reproductive age with polycystic ovary syndrome and 25 eumenorrheic women who were not taking hormonal contraceptives and who had a body mass index below 25 kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 60 publications
(59 reference statements)
1
22
0
Order By: Relevance
“…Studies by Schild et al [41] and Yaman et al [51] demonstrated no significant differences between endometrial thickness or endometrial volume measurements in patients who conceived compared with those who did not, but the studies did suggest that a minimal volume of 2.0-2.5 cm 3 was required for implantation to occur. This concept is supported by Raga et al [52], who assessed endometrial volume in 72 women on the day of embryo transfer, and noted that no pregnancies occurred in patients with an endometrial volume below 1 cm 3 and that implantation rates were significantly lower when the endometrial volume was less than 2 cm 3 . It is uncertain if volume measurements provide more predictive information than standard 2D measures of endometrial thickness as this has not been thoroughly assessed in randomized, blinded trials.…”
Section: Ovarian Reservesupporting
confidence: 65%
“…Studies by Schild et al [41] and Yaman et al [51] demonstrated no significant differences between endometrial thickness or endometrial volume measurements in patients who conceived compared with those who did not, but the studies did suggest that a minimal volume of 2.0-2.5 cm 3 was required for implantation to occur. This concept is supported by Raga et al [52], who assessed endometrial volume in 72 women on the day of embryo transfer, and noted that no pregnancies occurred in patients with an endometrial volume below 1 cm 3 and that implantation rates were significantly lower when the endometrial volume was less than 2 cm 3 . It is uncertain if volume measurements provide more predictive information than standard 2D measures of endometrial thickness as this has not been thoroughly assessed in randomized, blinded trials.…”
Section: Ovarian Reservesupporting
confidence: 65%
“…38 With the pioneering studies focused on Doppler, it was observed that resistance and pulsatility indices were very low in PCOS patients-related to good vascularization-but without changes throughout the cycle, this feature seems to be characteristic of PCOM, 21,38,39 although it is not internationally accepted. 39 This situation might change with the introduction of 3D digital Doppler angiography. 21,22 This new 3D US mode has allowed observing the following key events in this group of patients:…”
Section: Vascularization Of the Medullamentioning
confidence: 99%
“…30 This technique may be particularly useful for assessing ovarian anatomy in patients with polycystic ovarian syndrome because it allows improved evaluation of the size and the structure of the ovaries. By using 3DUS and CDI, Dolz et al 31 showed that, in comparison with ovulatory women with normal cycles, patients with polycystic ovarian syndrome have decreased resistive and pulsatility indices in the vasculature of the ovarian stroma, increased stromal vascularity that starts in the follicular phase and persists throughout the menstrual cycle, stromal vascular flow with peak systolic velocities similar to those in corpora lutea, and lack of luteal conversion.…”
Section: The Adnexa (Ovary and Fallopian Tube)mentioning
confidence: 99%
“…The value of volume measurements in infertility has been explored in a number of studies. 22,30,31 The utility of measurements of the ovary in polycystic ovarian syndrome and follicle size for better cycle monitoring has prompted a desire for more precise assessment of these irregularly shaped structures. Volume calculations of regular structures based on 2D variables are generally considered accurate, but for irregular structures, a more reliable and reproducible method of volume calculations must be used.…”
Section: The Adnexa (Ovary and Fallopian Tube)mentioning
confidence: 99%
See 1 more Smart Citation